Analisis Efektivitas Instalasi Pengolahan Air Limbah Domestik Studi Kasus Batikite Resort Jeneponto - Herlina Sattuang (Jurnal Ecosolum, 2020)
This study aims to analyze (1) the characteristics of wastewater in Batikite Resort (2) the design of wastewater treatment plants in accordance with the conditions of the Batikite Resort (3) the effectiveness of the wastewater treatment plant to actual liquid waste at the Batikite Resort. This research was conducted at Batikite Resort, Jeneponto Regency while the sample testing is done at the Makassar Center for Occupational Health and Safety (K3). The method used in this study is an experiment that is the manufacture of domestic wastewater treatment plants based on the results of laboratory scale research by Eryanto (2013) and test the effectiveness of equipment made based on the elimination of parameters for hotel domestic wastewater in the Minister of the Environment number 05 of 2014. The research data were analyzed descriptively presented in tabular form. Determination of BOD5, COD, phosphate, oil, ammonia, TSS and pH values is calculated according to the equation contained in the SNI Test Method. The effect of the treatment plant on treated water was analyzed using SPSS version 26 software. The results of the analysis of the effectiveness of the wastewater treatment plant made, shows that the wastewater treatment plant is very influential on the processed water allowance for BOD5 levels of 93.56%; COD 96.21%; phosphate 72.5%; 100% oil; ammonia 79.45%; TSS 97.23%; and the pH becomes 7.5. This wastewater treatment plant is quite effective in the Batikite Resort, but it requires the addition of activated charcoal to remove effluent odors.